Upaya Meningkatkan Pemahaman Siswa terhadap Materi Membaca Menggunakan Metode Resitasi pada Siswa Kelas IV SDN 10 Way Lima Pesawaran Tahun Ajaran 2021/2022 - Gustina, Okta; Supriyono, Supriyono; Saputra, Hendra (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2022)
: The purpose of this study was to improve student learning outcomes by applying the recitation method to reading material for grade 4 students SDN 10 Way Lima Pesawaran. The approach used in this study was a scientific approach with the recitation method. As for the steps of the recitation method, namely : (1) planning, (2) implementation, (3) observation and (4) reflection. Data collection techinques using observation sheets and students learning outcomes test. The data analysis technique used the formula for analyzing students learning outcomes and the percentage of completeness in student learning outcomes. The results of this study indicate that the apllication of the recitation method can improve students learning outcomes. Seen from the initial observatations with the number of students 17 students. Students learninf outcomes can increase thin can be seen from the student laerning outcomes test cycle 1 the average value at the first meeting is 5,23% and the second semester is 6,29%. Then in cycle 2 the implementation was only carried out once in a meeting with the test results cery clearly seen the improvement and had exceeded the standard of complete learning that had been determined by the Indonesian language education curriculum, which was an average of 6.70%.